Crop rotation. XX. Effects of winter leguminous crops on grain yield and some agronomic characteristics of corn - Santos, Henrique Pereira dos; Pottker, Delmar (Pesquisa Agropecuaria Brasileira, 2014)
During four years the effects of lupins (Lupinus albus L.), common vetch (Vicia sativa L.) and serradella (Ornithopus sativus Brot.) on corn (Zea mays L.) yields and some agronomic characteristics of corn were evaluated at the National Wheat Research Center (Brazil). Com was established under the no-till system in a complete randomized block design, with four replications. Corn was planted mechanically and hand harvested on plots of 120 m2. Corn yields, yield components (number of ears, number of kernels per plant and weight of kernels per plant), weight of 1,000 kemels and the height of the first ear, on the average, were not affected by the legumes. Plant height was influenced by the legumes during the last two years of this study. There were no significant differences on the levels of available nutrients and of organic matter of the soil samples taken immediately before corn planting. Common vetch showed to be the species with the greatest potential crop for use as an alternative for wheat in a rotation system